Assertions of Clarity & Raising Awareness. (9th October 2018) - Crone, Phil
Abstract: Barker & Taranto (2003) introduce the "paradox of asserting clarity, " arguing that any true assertion of the form It is clear that p should be necessarily uninformative. Assuming that the essential effect of assertions is to inform, it is therefore puzzling why any speaker would bother asserting the clarity of any proposition $p$ . I present a novel account of the semantics of clear that predicts assertions of clarity to be straightforwardly informative in some contexts, thereby partially resolving this paradox. However, on this account there remain cases in which clarity assertions are not obviously informative. I argue that in such cases, an assertion of the clarity of $p$ may play the role of raising awareness of $p$ or of evidence supporting $p$ . Raising awareness of $p$ may, in turn, have a number of downstream consequences; in particular, raising an addressee's awareness of an issue may have crucial effects on the addressee's resolution to decision problems. The effect of clarity assertions on agents' awareness states is formalized using a model of awareness in discourse inspired by Franke & de Jager (2007), de Jager (2009), and Franke & de Jager (2011) .